(untitled) (Proceedings of the YSU B: Chemical and Biological Sciences, 2003)
The perchlorate and nitrate anions, and also ion pairs Li+ClO^–_4 and Li+NO^–_3 have been studied by ab initio quantum chemical methods. Calculation of geometry and vibrational frequencies for the free anions and for monodentate, bidentate and tridentate structures of ion pairs has been performed at the RHF/6-31+G(d) and B3LYP/6-31+G(d) levels.